Diabetic Ketoacidosis as First Presentation of Latent Autoimmune Diabetes in Adult - Omar Nadhem; Essam Nakhla; Roger D. Smalligan (Case Reports in Medicine)
A 54-year-old white female with hypothyroidism presented with abdominal pain, nausea, vomiting, and diarrhea. She was found to have diabetic ketoacidosis (DKA) and admitted to our hospital for treatment. Laboratory workup revealed positive antiglutamic acid decarboxylase antibodies and subsequently she was diagnosed with latent onset autoimmune diabetes in adult (LADA). She was successfully treated with insulin with clinical and laboratory improvement. Diagnosis of LADA has been based on three criteria as given by The Immunology of Diabetes Society: (1) adult age of onset (>30 years of age); (2) presence of at least one circulating autoantibody (GADA/ICA/IAA/IA-2); and (3) initial insulin independence for the first six months. The importance of this case is the unlikely presentation of LADA. We believe that more research is needed to determine the exact proportion of LADA patients who first present with DKA, since similar cases have only been seen in case reports. Adult patients who are obese and have high blood sugar may deserve screening for LADA, especially in the presence of other autoimmune diseases. Those patients once diagnosed with LADA need extensive diabetic education including potentially serious events such as diabetic ketoacidosis.